When aggregation-induced emission meets protein aggregates - Tang, Sicheng (Natl Sci Rev, 2021)
There is an unmet demand for research tools to monitor the multistep protein aggregation process in live cells, a process that has been associated with a growing number of human diseases. Recently, AIEgens have been developed to directly monitor the entire protein aggregation process in test tubes and live cells. Future application of AIEgens is expected to shed light on both diagnosis and treatment of disease rooted in protein aggregation.